Household Income as A Factor in The Long-Term Liquidity of The Russian Banking Sector: Taking into Account Additional Factors - Olga S. MIROSHNICHENKO1; Valery V. GAMUKIN1; Natalia V. POKROVSKAIA2; Natalya S. VORONOVA2 (Communications of International Proceedings, 2020)
The article is devoted to the study of the income of individuals as a source of the long-term resource base of the Russian banking sector, for the period 1999-2019 and up to the beginning of 2020. It has been established that household deposits are the basis of long-term resources of the Russian banking sector. In the analyzed period, there are fluctuations in the share of long-term deposits of the population in bank liabilities, while the same indicator for the total deposits of individuals demonstrates positive dynamics, which required an analysis of a number of additional factors. It is noted that the introduction of the institution of compulsory deposit insurance had a stronger positive impact on the attraction of long-term deposits of the population by banks, in comparison with the attraction of total deposits of individuals. The influence of taxes on personal income on the structure of financial investments of the population was revealed. It is substantiated that changes in the personal income tax on investments in financial assets affect the investment preferences of the population. It is noted that in the context of a pandemic COVID-19, a reduction in long-term household deposits can have a negative impact on the long-term liquidity of the Russian banking sector. The relevance of the study of the impact of household deposits on the resource base of Russian banks is substantiated, taking into account the practice of taxation of personal income from investments in various financial assets.
Keywords: income of the population; deposits of the population; financial investments of the population; personal income tax; pandemic COVID-19.